2016
DOI: 10.1152/japplphysiol.01065.2015
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional control, but not subcellular location, of PGC-1α is altered following exercise in a hot environment

Abstract: The purpose of this study was to determine mitochondrial biogenesis-related mRNA expression, binding of transcription factors to the peroxisome proliferator-activated receptor-γ coactivator 1-α (PGC-1α) promoter, and subcellular location of PGC-1α protein in human skeletal muscle following exercise in a hot environment compared with a room temperature environment. Recreationally trained males (n = 11) completed two trials in a temperature- and humidity-controlled environmental chamber. Each trial consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 49 publications
6
24
4
Order By: Relevance
“…It was concluded that exercise intensity, rather than exercise volume, may be an important factor affecting exerciseinduced changes in nuclear PGC-1α protein content. These suggestions are confirmed when pooling results from the available literature, which indicates that a single session of MICE at ~55 to 75% of Ẇmax does not induce a large increase (~1 to 1.5-fold) in nuclear PGC-1α protein content [14,86,[91][92][93], whereas all-out SIE is associated with larger increases (~1.7 to 2.3fold), despite much lower exercise volumes [14,15]. Further research is required to confirm these hypotheses and to characterize the effects of exercise volume on PGC-1α subcellular localization.…”
Section: Exercise-induced Changes In Nuclear Pgc-1α Protein Contentsupporting
confidence: 57%
See 1 more Smart Citation
“…It was concluded that exercise intensity, rather than exercise volume, may be an important factor affecting exerciseinduced changes in nuclear PGC-1α protein content. These suggestions are confirmed when pooling results from the available literature, which indicates that a single session of MICE at ~55 to 75% of Ẇmax does not induce a large increase (~1 to 1.5-fold) in nuclear PGC-1α protein content [14,86,[91][92][93], whereas all-out SIE is associated with larger increases (~1.7 to 2.3fold), despite much lower exercise volumes [14,15]. Further research is required to confirm these hypotheses and to characterize the effects of exercise volume on PGC-1α subcellular localization.…”
Section: Exercise-induced Changes In Nuclear Pgc-1α Protein Contentsupporting
confidence: 57%
“…Research in human skeletal muscle demonstrates the exercise-induced accumulation of PGC-1α protein in the nucleus takes place before increases in the cytosol [14,15,86,91]. Studies have attributed this increase to increased PGC-1α protein stability mediated by p38 MAPK and/or AMPK [14,15,86], and/or greater nuclear import from, or decreased nuclear export to, the cytosol of existing PGC-1α protein [15,86,91]. Regardless, the early accumulation of PGC-1α protein in the nucleus has been linked with an increase in the activity of existing PGC-1α protein, an event that may mediate the initial phase of exercise-induced mitochondrial biogenesis [14,15,89].…”
Section: Exercise-induced Changes In Nuclear Pgc-1α Protein Contentmentioning
confidence: 99%
“…We observed a significant exercise-induced increase in PGC-1α protein content in both the nuclear and cytosolic fractions Pre-HVT, consistent with most previous research (24, 33, 43, 44). However, for the first time we report that these exercise-induced increases were absent post training in both subcellular fractions.…”
Section: Discussionsupporting
confidence: 92%
“…Peroxisome proliferator-activated receptor γ coactivator-1α (PGC-1α) is a key regulator of exercise-induced mitochondrial biogenesis (74) (for an in-depth analysis of the effects of exercise on mitochondrial biogenesis mediated by PGC-1α [and p53] the reader is referred to some excellent reviews; (17, 21, 35, 64)). In both rat (73) and human (24, 33, 43, 44) skeletal muscle, it has been observed that there is a post-exercise increase of PGC-1α protein content in the nucleus, where PGC-1α performs its transcriptional activity (62). Changes in PGC-1α protein content (30), as well as the content of other proteins (e.g., p53 (36)), contribute to the exercise-induced upregulation of PGC-1α mRNA (58).…”
Section: Introductionmentioning
confidence: 99%
“…Trials consisted of 3 h of sitting in an environmentally controlled chamber (Darwin Chambers Company, St. Louis, MO) at three different temperatures (33 °C, 7 °C, and 20 °C) each at 60% relative humidity. The temperatures were determined in order to make a direct comparison to a previous study including the exercise stimulus (Heesch et al 2016). Each trial was separated by approximately one week.…”
Section: Methodsmentioning
confidence: 99%